Screening for age-related macular degeneration using nonstereo digital fundus photographs. - Jain, S; Hamada, S; Membrey, W; Chong, V (2006)
Age-related macular degeneration (AMD) is a disease with significant visual morbidity and accounts for the majority of blind registrations in the developed world including the UK. Certain forms of neovascular AMD are amenable to treatment but require expeditious referral to a retinal specialist. AIM: To evaluate the possibility of using nonstereo fundus photographs as a low-cost screening tool for neovascular AMD. DESIGN: Retrospective review of patients referred to the macular clinic of a teaching hospital in London. METHODS: A total of 198 randomised digital fundus photographs, without any other clinical information, were presented to two independent ophthalmic interns who graded them into one of the three categories: normal, age-related maculopathy (ARM), or neovascular age-related macular degeneration (AMD) to determine the urgency of referral to clinic. The results were compared with the known diagnosis for each patient and sensitivities and specificities for each diagnostic category calculated. RESULTS: The intraobserver Kappa statistic was 0.75 and 0.91 for grader 1 and 2, respectively. The interobserver Kappa was 0.54. The mean sensitivity and specificity for the identification of ARM was 60.5 and 76.3%, respectively The mean sensitivity and specificity for the identification of AMD was 85.7 and 78.8%, respectively. CONCLUSION: Nonstereo digital fundus photograph is a reasonable screening tool for CNV and may aid in decreasing the visual morbidity it causes by enabling timely referrals and treatment.